Harga Saham Kini: Dalam Bayang-bayang Fundamental - Sari Gabe Sagala; Mochamad Muslih (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This study aims to determine the effect of liquidity, funding policies, and financial performance on the stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange (BEI) for the 2009-2018 period. The theory tested in this research is signaling theory. This research uses quantitative methods. The research variables are stock price, company liquidity, funding policy, and financial performance. The data used are secondary data taken from the Indonesia Stock Exchange (IDX). The population in this study is pharmaceutical companies listed on the Indonesia Stock Exchange. The research sample is 7 (seven) pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period 2009-2018. The results showed that company liquidity had no significant effect on stock prices, funding policies had no significant effect on stock prices, and financial performance had no significant effect on stock prices. The results of this study add to the outer layer of knowledge building according to Imre Lakatos. The implication of this research is that the company's fundamental conditions do not necessarily affect stock prices, depending on the type of stock market. It is recommended to investors to be more careful in observing the factors that influence stock prices in the 4.0 industrial revolution era. Next researchers are advised to use other fundamental aspects as their independent variables so that more fundamental elements of the company are examined in relation to stock prices in the 4.0 industrial revolution era.